Mezcala community and ethnic recreation in neoliberal globalization - Santiago Bastos (CUHSO)
The confl ict in which it is embedded Mezcala about threats to their community land is part ofa renewal of the idea of community and content of ethnic identity. In face to the collapse of the postrevolutionary,which sheltered the territoriality of Mezcala, the new proposals associated with the idea ofindigenous peoples-in this case Coca-Pueblo are helping to renew the land rights and self-government butalso the contents of being indigenous and community life.